2014
DOI: 10.1080/0144929x.2014.964319
|View full text |Cite
|
Sign up to set email alerts
|

Understanding user motivation for evaluating online content: a self-determination theory perspective

Abstract: Abstract:In a digital society, people have access to all kinds of electronic information as online users. They have also contributed various content for exchanging ideas in the online community, which has not only extended the traditional knowledge sharing channels, but has also led to concerns about content quality and reliability. The literature suggests that user involvement in collaboratively evaluating the quality of online content for an online community is likely to be an effective means to ease these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…2. Prior literature used SDT to study continuance and contribution [91,92]. Although similarly drawing on SDT, our study differs from prior research.…”
Section: Notesmentioning
confidence: 99%
“…2. Prior literature used SDT to study continuance and contribution [91,92]. Although similarly drawing on SDT, our study differs from prior research.…”
Section: Notesmentioning
confidence: 99%
“…Prior studies have examined intrinsic and extrinsic motivation from different perspectives in various research fields. According to Zhang et al [73], determinants such as identified motivation, introjected motivation, and external motivation have crucial influences on users' intention to evaluate online content collaboratively. Kelley and Alden [74] used SDT to examine the internalization of brand identity by its online community members through the interactivity of the brand website.…”
Section: Self-determination Theorymentioning
confidence: 99%
“…They are random users, some can be opinion leaders or celebrities, but some can be malicious users without any expertise (Zhang et al, 2016). They may have different backgrounds, beliefs and motivations as opposed to professionals (Zhang et al, 2015;Bertot et al, 2012). Even if there are some experts and authorities on social media, the degree to which each information producer can be believed remains unclear (Flanagin and Metzger, 2013).…”
Section: Peripheral Route Of Digital Libraries and Social Mediamentioning
confidence: 99%